Media and environment: how indonesia online news portal frames biodegradable issue? - Yuliarti, Monika Sri; Jatimurti, Wikan (Faculty of Communications Science, Dr. Soetomo University, 2019)
Environmental problems are still an important issue and cannot be resolved completely until now, even after the 1970s the United Nations established a world environmental day. Plastic waste is considered the most responsible for the problems of environmental damage today. Therefore, an innovation that comes from biodegradable material, with its biodegradable product is considered to be the answer to this environmental problem. This study examines how reporting on the environment is framed in online mass media, especially in relation to biodegradable material and biodegradable products. This is qualitative research, with the object of two Indonesian online news sites, namely www.detik.com and www.okezone.com. Data collection techniques used is document studies and data analysis techniques employed is Robert N. Entman's Framing analysis model which involves four elements, namely: define problems, diagnose causes, make moral judgment, and treatment recommendation. The findings of this study are that environmental issues have not dominated online media coverage, and the biodegradable issue has not been framed thoroughly by online media.